Comparative pharmacokinetic study of the five anti-inflammatory active ingredients of Inula cappa in a normal and an LPS-induced inflammatory cell model - Huang, Jing; Chen, Ruixing; Zhou, Jie; Zhang, Qing; Xue, Cun; Li, Yueting; Zheng, Lin; Huang, Yong; Wang, Qun; Chen, Yi; Gong, Zipeng (Frontiers in Pharmacology, 2022)
Inula cappa is a commonly used medicine in the Miao area of Guizhou Province in China. We established an in vitro inflammatory model of mouse macrophage RAW264.7 cells to study the different pharmacokinetics of five anti-inflammatory active ingredients in the I. cappa extract namely luteolin (LUT), chlorogenic acid (CA), cryptochlorogenic acid (CCA), 3,4-dicaffeoylquinic acid (3,4-DCQA) and 4,5-dicaffeoylquinic acid (4,5-DCQA), in a normal and an inflammatory cell model. First, RAW264.7 cells were treated in vitro with l μg/mL lipopolysaccharide ( LPS ) for 24 h to establish an inflammatory cell model. Then, the pharmacokinetic characteristics of the five ingredients were compared in normal and inflammatory cells after treatment with 200 µg/mL and 800 µg/mL of I. cappa extracts. After treatment with 1μg/mL LPS for 24 h, the volume of RAW264.7 cells was increased, the morphology was changed, the antennae were obv-ious, and the secretion of inflammatory factors NO and TNF-α was increased. The pharmacokinetics results showed that the five ingredients in normal and inflammatory cells exhibited an increase in Cmax and AUC values with increasing doses, and the Cmax and AUC values of five ingredients were positively correlated with the extract concentration. Each of these five ingredients presented nonlinear pharmacokinetic characteristics. After treatment with 200 µg/mL of I. cappa extract, the uptake of five ingredients increased in inflammatory cells, Tmax was prolonged, MRT and t1/2 were prolonged, and CL_F and Vz_F were decreased, while after treatment with 800 µg/mL of I. cappa extract, the uptake of five ingredients decreased, Tmax was prolonged, absorption was faster, and MRT and t1/2 were prolonged. The five analyzed components in I. cappa extract exerted different effects on normal cells and LPS-induced inflammatory cells. Compared to normal cells, the uptake of five ingredients in inflammatory cells was faster and the AUC and Cmax values increased with increasing doses, showing a dose-dependent nonlinear pharmacokinetic profile. These results indicate that the pharmacokinetic effects of the five analyzed ingredients in I. cappa extract are changed in the inflammatory state.